Cryo-EM Structure of Caspase-8 Tandem DED Filament Reveals Assembly and Regulation Mechanisms of the Death Inducing Signaling Complex - Fu, Tian-Min (Mol Cell, 2016)
Caspase-8 activation can be triggered by death receptor-mediated formation of the death-inducing signaling complex (DISC) and by the inflammasome adaptor ASC. Caspase-8 assembles with FADD at the DISC and with ASC at the inflammasome through its tandem death effector domain (tDED), which is regulated by the tDED-containing cellular inhibitor cFLIP and the viral inhibitor MC159. Here we present the caspase-8 tDED filament structure determined by cryo-electron microscopy. Extensive assembly interfaces not predicted by the previously proposed linear DED chain model were uncovered, and further confirmed by structure-based mutagenesis in filament formation in vitro, and Fas-induced apoptosis and ASC-mediated caspase-8 recruitment in cells. Structurally, the two DEDs in caspase-8 use quasi-equivalent contacts to enable assembly. Using the tDED filament structure as a template, structural analyses reveal the interaction surfaces between FADD and caspase-8, and the distinct mechanisms of regulation by cFLIP and MC159 through comingling and capping, respectively.